(untitled) (Revista Educação, Artes e Inclusão, 2025)
This text is a report on an artistic-pedagogical project entitled Respiradores, carried out between the months of February and July 2022, at the Bernardo Valadares de Vasconcellos State School, in Sete Lagoas-MG. All stages of the project were detailed, from pre-production, production and post-production, accompanied by photographic and videographic records, in addition to the project’s final documentary, which, on this occasion, was supported by the 1st Edition of the Museu é Mundo Award. With the aim of promoting reflection on art, education and sustainability, in addition to describing the step-by-step process of carrying out the project at school, a brief historical overview of environmental education from the 1970s onwards, both in Brazil and around the world, was included.